Sequestro De Carbono Emareas Cultivadas Com Eucalipto Em Diferentes Idades Na Região Oeste Da Bahia 2017
DOI: 10.31692/2526-7701.iicointerpdvagro.2017.00126
|View full text |Cite
|
Sign up to set email alerts
|

Sequestro De Carbono Emareas Cultivadas Com Eucalipto Em Diferentes Idades Na Região Oeste Da Bahia

Abstract: ResumoA conversão de sistemas naturais em sistemas agrícolas envolve uma série de atividades que levam a perturbação do solo o que influencia diretamente nas taxas de decomposição da matéria orgânica e, por conseguinte ocasionandoalteraçõesnosteores e estoques de carbono.Portanto objetivou-se com esse estudo, avaliar a influência do plantio de eucalipto com diferentes idades sobre os estoques de carbono no solo e CO 2 equivalente como também acumulo de carbono na biomassa vegetal e serrapilheira. O aumento das… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…In his study, Balin (2017) found that the higher TOC content in the EUC area is possibly due to the greater contribution of crop residues deposited on the surface. Similar results were found by Rosa et al (2017) when carrying out studies with eucalyptus plantations at different ages and native savannah area, according to the authors, this fact is not related only to the deposition of organic material, but also to the age of cultivation. Among the areas, the APB presented higher TOC contents when compared to SAFs in the layer below 20 cm.…”
Section: Resultssupporting
confidence: 83%
“…In his study, Balin (2017) found that the higher TOC content in the EUC area is possibly due to the greater contribution of crop residues deposited on the surface. Similar results were found by Rosa et al (2017) when carrying out studies with eucalyptus plantations at different ages and native savannah area, according to the authors, this fact is not related only to the deposition of organic material, but also to the age of cultivation. Among the areas, the APB presented higher TOC contents when compared to SAFs in the layer below 20 cm.…”
Section: Resultssupporting
confidence: 83%